Condensing Test of R404A Outside Horizontal Enhanced Tubesand Method of Data Processing - Ouyang Xinping; Yuan Daoan; Zhang Tongrong (Zhileng xuebao)
Condensation of refrigerant R404A on doubly-enhanced tubes and convection heat transfer of water inside tube were measured and analyzed. The experimental data were processed by Wilson graphical method and Gnielinski method. Theoretical analysis and experimental studies show that the Gnielinski method is more appropriate to process the experiment data of doubly-enhanced tubes inside and outside surface heat transfer coefficients than the Wilson graphical method which will engender great error. The correlations of convective heat transfer inside tube and condensation heat transfer outside tube were obtained. The heat transfer enhancement ratios of inside and outside tube are 2.17 and 7.91, respectively. The condensation surface heat transfer coefficients of non-azeotropic refrigerant R404A on enhanced tubes increase with increasing wall subcooling degree which present a different variation trend from pure refrigerants condensation on smooth tubes. That is mainly due to the vapour diffusion layer formed between the liquid film and the vapour bulk.